2023
DOI: 10.3389/fped.2023.1224113
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic appendectomy versus traditional three-hole laparoscopic appendectomy for acute appendicitis in children by senior pediatric surgeons: a multicenter study from China

Abstract: ObjectiveThe aim of this study was to evaluate the clinical efficacy of single-incision laparoscopy appendectomy (SILA) and traditional three-hole laparoscopy appendectomy (THLA) for the treatment of acute appendicitis in children.MethodsThe clinical data of children (<14 years old) who underwent laparoscopic appendectomy at Yijishan Hospital of Wannan Medical College, Hubei Provincial Maternal Health Hospital and Qingdao Women and Children's Medical Center from January 2019 to June 2022 were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a narrow space, robotic surgery provided huge operational scope, and has the experience of successful anastomosing 2 mm accessory hepatic ducts ( 17 ). In recent years, many studies at home and abroad have shown that, compared with traditional laparoscopy, robotic surgery has unique advantages in terms of reduced postoperative anastomotic complications (such as biliary fistula and anastomotic stenosis) ( 18 ), but there is still a lack of large-sample research. In this context, by comparing the operations performed by the same group of doctors in the same period, we found that the amount of bleeding, the time of indwelling abdominal drainage tube [10 (8–12) vs. 15 (11.5–18) days, p < 0.05], the fasting time [4 (3–4) vs. 6 (5–7) days, p < 0.05], and the hospitalization time [6 (5–7) vs. 8 (6–10) days, p < 0.05] were all significantly lower than those of laparoscopy and inseparable from the advantages of robotic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a narrow space, robotic surgery provided huge operational scope, and has the experience of successful anastomosing 2 mm accessory hepatic ducts ( 17 ). In recent years, many studies at home and abroad have shown that, compared with traditional laparoscopy, robotic surgery has unique advantages in terms of reduced postoperative anastomotic complications (such as biliary fistula and anastomotic stenosis) ( 18 ), but there is still a lack of large-sample research. In this context, by comparing the operations performed by the same group of doctors in the same period, we found that the amount of bleeding, the time of indwelling abdominal drainage tube [10 (8–12) vs. 15 (11.5–18) days, p < 0.05], the fasting time [4 (3–4) vs. 6 (5–7) days, p < 0.05], and the hospitalization time [6 (5–7) vs. 8 (6–10) days, p < 0.05] were all significantly lower than those of laparoscopy and inseparable from the advantages of robotic surgery.…”
Section: Discussionmentioning
confidence: 99%